Gut analysis of small non-volant mammals of Mt. Makiling, Luzon Island, Philippines - De Guia, Anna Pauline O.; Quibod, Ma. Niña Regina M (2014)
Three non-native species (Ratus exulans, R. tanezumi and musculus) of small non-volant mammals were recorded along various elevational gradients of Mount Makiling. Invertebrate remains and plant matter comprised the bulk of their diets based on the food items identified. The identified plant matter were leaves and seeds while invertebrates were easily identifiable through body parts such as legs, head and antennae. Other contents identified including vertebrate remains such as hair/fur, feathers and bones, plastics, rubber, stones, and intestinal worms were noted. Based on the calculated relative abundance of each food type, there is no significant difference in the diets of the three non-native rodent species Preliminary results suggest that introduced rodents in Mt. Makiling have broad diets and there is no indications that their main diet includes native wildlife species. Traces of vertebrate remains, however, may indicate potential predation on wildlife species and further studies are needed to clarify this.
Keywords: Mammals -- Mount Makiling (Laguna)